The role of N-glycosylation of CD200-CD200R1 interaction in classical microglial activation - Chao Liu; Yifen Shen; Ying Tang; Yongchun Gu (BMC, 2018)
Abstract Background Microglial inflammatory activation is the common feature of the central nervous system (CNS) diseases. Microglia can be activated and particularly polarized toward a dual role in the injured CNS. The CD200 receptor 1 (CD200R1) inhibits inflammatory microglia activation as illustrated by studies. Publications show abnormal activation of microglia secondary to the deficient inhibit of CD200-CD200R interaction. In the present study, we established a neuronal-microglia co-culture system to investigate the association between CD200R1 engagement and classical microglial activation. We analyzed the glycosylation of CD200R1 and the CD200 binding. Secretion of pro-inflammatory cytokines were measured. Results CD200R1 was N-glycosylated at Asparagine 44 (Asn44, N44). Mutation of this site disrupted CD200-CD200R1 interaction and up-regulated the expression of cytokines iNOS, CD86, IL-1β and TNF-α. Conclusion N44 of CD200R1 is a significant binding site for CD200-CD200R1 interaction and play a critical role in the maintenance of microglia. The N-glycosylation of CD200R1 could serve as a therapeutic agent for CNS inflammation.